2014
DOI: 10.1111/jog.12634
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overnight oximetry findings on cardiac autonomic modulation in women during second trimester of uncomplicated pregnancy

Abstract: Parasympathetic activities of cardiac autonomic modulations might be attenuated in women who experience profound night-time oxygen desaturation, even if the incidence of significant events is quite low. The oximetry finding of minimum SaO2  ≤ 90% might be a valuable criterion for clinically meaningful sleep-disordered breathing among women with early uncomplicated pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…No women had an ODI ≥5.0 in our previous survey of uncomplicated pregnancies during the second trimester. 30 Therefore, the risk of OSA might increase during late pregnancies. 11,12 Patients A and B with ODI ≥5.0 and minimum SpO 2 of <90% were thought to undergo quite severe hypoxia during nocturnal sleep, and they both developed GH after 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…No women had an ODI ≥5.0 in our previous survey of uncomplicated pregnancies during the second trimester. 30 Therefore, the risk of OSA might increase during late pregnancies. 11,12 Patients A and B with ODI ≥5.0 and minimum SpO 2 of <90% were thought to undergo quite severe hypoxia during nocturnal sleep, and they both developed GH after 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Watanabe et al. 16 tried to answer this question hypothesizing that autonomic modulations might be associated with (and possibly be a predictor of) SDB.…”
Section: Impact Of Overnight Oximetry Findings On Cardiac Autonomic Mmentioning
confidence: 99%
“…Watanabe et al. 16 correctly analyzed LF and HF which reflect the combination of the sympathetic and the parasympathetic nervous system influences and vagal activity respectively; however, no data are available on very LF (measures rhythms between every 25 s and every 5 min) which is particularly exaggerated by SDB. Moreover, other sleep disturbances can influence the sympathetic–parasympathetic balance; sleep deprivation for instance is very common among pregnant women.…”
Section: Impact Of Overnight Oximetry Findings On Cardiac Autonomic Mmentioning
confidence: 99%
“…A previous small study showed higher levels of interleukin (IL)-6 and IL-8, in 4 women with GDM and OSA compared to 21 women without OSA [ 12 ]. Moreover, a small study found decreased heart rate variability in pregnant women, a non-invasive marker of attenuation of parasympathetic activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%